Muscle fascicle and tendon behavior during human locomotion revisited - Ishikawa, M.; Komi, P. V. (Exercise and Sport Sciences Reviews, 2008)
High-speed ultrasonography has revealed that, in human locomotion, the nature of fascicle and tendon length changes varies depending on the task, contraction intensity, and the muscles involved. The findings emphasize that the active fascicles of the gastrocnemius muscle are suddenly stretched, although they are shortening. This short-lasting stretch triggers the stretch reflex, timing of which is dependent on running speed.